2014
DOI: 10.1212/wnl.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Retinal architecture and mfERG

Abstract: Objective: To describe a novel neurophysiologic signature of the retinal ganglion cell and to elucidate its relationship to abnormalities in validated structural and functional measures of the visual system. Methods:We used multifocal electroretinogram-generated optic nerve head component (ONHC) responses from normal subjects (n 5 18), patients with multiple sclerosis (MS) (n 5 18), and those with glaucoma (n 5 3). We then characterized the relationship between ONHC response abnormalities and performance on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
(42 reference statements)
2
12
0
Order By: Relevance
“…73 It has been shown that by modification of the MF-ERG test protocol it is possible to visualize an additional component of the MF-ERG, the optic nerve head component (ONHC), which is generated at the optic nerve head. 74 Recent work has shown a significantly increased number of abnormal ONHC responses in MS patients with a history of unilateral ON compared with normal subjects; ONHC abnormalities were also present (albeit reduced in number) in the fellow eyes of the same patients. 74 The number of abnormal ONHC responses appears to correlate strongly with RNFL thickness, so that a 10-µm reduction in RNFL thickness is associated with 6.8 additional abnormal ONHC responses (from 103 responses).…”
Section: Relationship Of Oct Parameters With Clinical Outcome Measuresmentioning
confidence: 97%
See 2 more Smart Citations
“…73 It has been shown that by modification of the MF-ERG test protocol it is possible to visualize an additional component of the MF-ERG, the optic nerve head component (ONHC), which is generated at the optic nerve head. 74 Recent work has shown a significantly increased number of abnormal ONHC responses in MS patients with a history of unilateral ON compared with normal subjects; ONHC abnormalities were also present (albeit reduced in number) in the fellow eyes of the same patients. 74 The number of abnormal ONHC responses appears to correlate strongly with RNFL thickness, so that a 10-µm reduction in RNFL thickness is associated with 6.8 additional abnormal ONHC responses (from 103 responses).…”
Section: Relationship Of Oct Parameters With Clinical Outcome Measuresmentioning
confidence: 97%
“…74 Recent work has shown a significantly increased number of abnormal ONHC responses in MS patients with a history of unilateral ON compared with normal subjects; ONHC abnormalities were also present (albeit reduced in number) in the fellow eyes of the same patients. 74 The number of abnormal ONHC responses appears to correlate strongly with RNFL thickness, so that a 10-µm reduction in RNFL thickness is associated with 6.8 additional abnormal ONHC responses (from 103 responses). 74 The relationship between the ONHC and other OCT parameters remains unclear at this time.…”
Section: Relationship Of Oct Parameters With Clinical Outcome Measuresmentioning
confidence: 97%
See 1 more Smart Citation
“…80 This was chosen for analysis because the normal ONHC response depends on the integrity of the RGC neuron, and is representative of the action potential as RGC axons traverse the lamina cribosa and conduction switches from unmyelinated to myelinated axons. This study found a significant reduction in ONHC responses in MS eyes with worse scores for LCLA.…”
Section: Psychometric Validitymentioning
confidence: 99%
“…[11][12][13] Of interest, previous studies have found that the clinically unaffected contralateral eye may display some degree of dysfunction following unilateral ON. [14][15][16] Structural data to date are only available for the outer retina over 6 months after ON 17 or for the inner retina over 12 months. 18 Although a number of cross-sectional OCT studies in ON have been published, 8,19 longitudinal studies are still scarce.…”
mentioning
confidence: 99%